الفصل عن طريق المبادلات الأيونية واستعمالها في تنقية المياه(Ion Exchange - حفصي, عائشة; فقير, الجبارية (جامعة الوادي University of Eloued, 2017)
إن الهدف من هذه الدراسة هو إثبات فاعلية المبادل الأيوني في تنقية المياه الجوفية لتقليل تراكيز المواد غير المرغوب فيها وخاصة تلك التي تشكل خطرا على صحة الانسان. حيث استخدمنا في دراستنا للمياه الجوفية على مستوى « جامعة الشهيد حمه لخضر بالواد » نوع من المبادلات الايونية لغرض تنقيتها وقد حققت نتائج مخبرية مقبولة حيث كانت كما يلي: تركيز الكالسيوم (قبل mg/l 262 وبعد mg/l 112) وتركيز المغنيزيوم (قبل mg/l 118 وبعد mg/l 70) وتركيز الكلور(قبل mg/l 735 وبعد mg/l 117.6) تركيز الفلورايد يساوي (قبل mg/l2.76 و بعد mg/l(1.05 و القساوة الكليةTH (f°) تساوي (قبل38و بعد 23). The objective of this study is to demonstrate the effectiveness of the ion exchanger in the purification of groundwater to reduce concentrations of unwanted substances, especially those that pose a threat to human health. We used in our study of groundwater at a level of «University of ShaheedHammaLakhdar El -Ouaed» type of ion exchangers for the purpose of purification and has achieved laboratory results were acceptable as follows: Calcium concentration (before 26 mg / l and after 112 mg / l), Magnesium concentration (before 118 mg / l and after 70 mg / l),Chlorine concentration (before 735mg / l and after 117.6 mg / l) ,the concentration of fluoride is equal to (2.76 mg / l and after 1.05 mg / l) and the total hardness TH (f °) is equal to (before 38 and after 23).
مذكرة ماستر تخصص هندسة كيميائية
Keywords: Purification de l'eau, échanged'ions, eau contaminée, dureté de l'eau, fluorure; تنقية المياه, التبادل الايوني, المياه الملوثة, قساوة المياه, الفلورايد